Twisted - Hardt, Helen (Hardt, Helen. Steel brothers saga, 2017)
Ryan Steel, his world recently upended by an earth-shattering secret, now faces yet another potential revelation surrounding the Steel family mystery. He no longer fully trusts his siblings or the woman he loves. He's alone---alone and terrified and immersed in a conundrum that becomes more twisted each day. Ruby Lee loves Ryan and desperately wants to help him. She'll do whatever she must to see him through this troubling time, but her own shrouded past still haunts her, and she's determined to put an end to both of their mysteries once and for all. But the more she uncovers, the more danger she's in...and she may lose Ryan forever.